The Construction of Muslim Terrorism in the Kingdom Movie 2007 Directed by Peter Berg: A Reception Theory - Santoso, Agung Budi, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
This study belongs to the literary study. This study analyzes the construction of Muslim terrorism based on reader response reflected in The Kingdom Movie (2007). There are two objectives of the study, the first is to describe the dominant issues by the reviewers in applying reader response theory to Peter Berg's The Kingdom movie, and the second is to explain the reason why the dominant issue are perceived differently by reviewers. This study is a qualitative study and using two data sources; they are primary and secondary data. The primary data source is the reviews of The Kingdom movie (2007) by Peter Berg from IMDb (Internet Movie Database). The secondary data of this study are taken from other sources such as literary book, previous studies, articles, journals, and also website related to reader response theory. This study aimed to reveal how the cultural reader response reflected to The Kingdom movie. The dominant issue which is respond by the reviewers is the terrorism dealing with the culture reader response.